Ultrasonic measurements in the 1-(trans-4-hexylcyclohexyl)-4-isothiocyanatobenzene near the nematic-isotropic transition - Balcerzak, A. (Archives of Acoustics, 2005)
The absorption and velocity of ultrasonic longitudinal waves in the nematic liquid crystal 1-(trans-4-hexylcyclohexyl)-4-isothiocyanatobenzene (6CHBT) have been measured as a function of temperature between 24oC and 55oC at 5.2 MHz. The temperature dependence of ultrasonic absorption has a sharp maximum, whereas that dependence of velocity shows a local minimum in the region of the nematic-isotropic (N-I) phase transition. Additional temperature measurements of density have been done to calculate the thermal coefficient of expansion and the temperature coefficient of adiabatic compressibility. Both these parameters exhibit critical behaviour at the transition which has been analysed. The values of the exponent determining the growth of the order fluctuations have been calculated and compared with references.